Effect of depression and anxiety on the success of pelvic floor muscle training for pelvic floor dysfunction. (October 2013) - Khan, Z. A.; Whittal, C.; Mansol, S.; Osborne, Lisa A.; Reed, P.; Emery, S.
<x xml:space="preserve">Abstract</x> The objective of this study was to determine the impact of the psychiatric symptoms of anxiety and depression, as assessed by validated questionnaires on the success of pelvic floor muscle training (PFMT). A prospective observational study was carried out by the Uro-gynaecological Physiotherapy Department at the Singleton Hospital, Swansea. A total of 108 consecutive women with pelvic floor dysfunction were referred for physiotherapy and admitted to the 6-month physiotherapy programme. They underwent subjective and objective assessments of their pelvic floor and psychological health at the beginning and end of the programme. A strong correlation was noted between the severity of anxiety and depression symptoms and the severity of their pelvic floor dysfunction. Following physiotherapy, apart from sexual function, all domains of pelvic floor dysfunction showed significant improvement. Based on the severity of their anxiety/depression symptoms, the patients were stratified into three groups. The group of patients that benefitted most had either no or only mild anxiety/depression. This study raises the question of whether a targeted approach should be undertaken for managing patients who, in addition to their pelvic floor dysfunction, demonstrate psychiatric symptoms.